The spirit ambulance: choreographing the end of life in Thailand - Stonington, Scott (California series in public anthropology, 2020)
"The Spirit Ambulance is a journey into decision-making at the end of life in Thailand, where families attempt to craft good deaths for their elders in the face of clashing ethical frameworks, from a rapidly developing universal medical system, to national and global human-rights politics, to contemporary movements in Buddhist metaphysics. Stonington's gripping ethnography documents how Thai families attempt to pay back a "debt of life" to their elders through intensive medical care, followed by a medically-assisted rush from the hospital to home to ensure a spiritually advantageous last breath. The result is a powerful exploration of the nature of death and the complexities arising from the globalization of biomedical expertise and ethics around the world"--